Effects of different ratios of nitrogen base fertilizer to topdressing on soil nitrogen form and enzyme activity in sugar beet under shallow drip irrigation - Li, Zhi; Jian, Caiyuan; Guo, Xiaoxia; Tian, Lu; Han, Kang; Li, Yinghao; Zhang, Peng; Kong, Dejuan; Ren, Huimin; Jiaerdemulati, Alehesi; Wang, Zhenzhen; Liu, Huiyu; et al. (PeerJ, 2024)
Sugar beets account for 30% of global sugar production each year, and their byproducts are an important source of bioethanol and animal feed. Sugar beet is an important cash crop in Inner Mongolia, China. To achieve high yields and sugar content, it is essential to supply nitrogen fertilizer in accordance with the growth characteristics of sugar beet, thereby enhancing the efficiency of nitrogen fertilizer utilization. A two-year experiment was carried out in the experimental field of the Inner Mongolia Academy of Agricultural & Animal Husbandry Sciences. The impact of varying ratios of nitrogen-based fertilizer to topdressing on nitrate nitrogen and ammonium nitrogen levels in the 20–60 cm soil layer, as well as the activities of protease, urease, catalase, and sucrose in the 20–40 cm soil layer were investigated during the rapid leaf growth period and root and sugar growth period. Results indicated that different ratios of nitrogen-based fertilizer to topdressing significantly influenced the levels of nitrate nitrogen and ammonium nitrogen, and the activities of protease and urease in the 0–20 cm soil layer, with these effects diminishing as soil depth increased. The activities of catalase and sucrose were minimally impacted. Nitrogen was applied at 150 kg/ha during the growth period of sugar beet, according to the growth characteristics of sugar beet to maximize nitrogen utilization efficiency. Topdressing was completed with irrigation at the rapid growth stage. The nitrogen-based fertilizer to topdressing ratio of 6:4 resulted in optimal crop yield and sugar yield of sugar beet under shallow drip irrigation. Additionally, the activities of protease and urease in different soil treatments were significantly different, and the activities of protease and urease in the 0–40 cm soil layer were identified as useful soil physiological indicators for nitrogen utilization in sugar beet.
Keywords: Sugar beet; Nitrate nitrogen; Ammonium nitrogen; Soil enzyme activity; Yield